The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/glia.24311
|View full text |Cite
|
Sign up to set email alerts
|

Piezo1 channel‐mediated Ca2+ signaling inhibits lipopolysaccharide‐induced activation of the NF‐κB inflammatory signaling pathway and generation of TNF‐α and IL‐6 in microglial cells

Abstract: Microglial cells are crucial in maintaining central nervous system (CNS) homeostasis and mediating CNS disease pathogenesis. Increasing evidence supports that alterations in the mechanical properties of CNS microenvironments influence glial cell phenotypes, but the mechanisms regulating microglial cell function remain elusive.Here, we examined the mechanosensitive Piezo1 channel in microglial cells, particularly, how Piezo1 channel activation regulates pro-inflammatory activation and production of pro-inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 79 publications
1
15
0
Order By: Relevance
“…Activation of Piezo1 exerts an anti-inflammatory effect through inhibition of the NF-κB pathway, but not the extracellular signal-regulated kinase (ERK) and p38 pathways (Malko et al, 2023). Consistent with this, showed that inhibition of Piezo1 promotes LPSmediated secretion of pro-inflammatory cytokines from microglia.…”
Section: Piezo1 Regulates the Inflammatory Phenotype Of Microgliasupporting
confidence: 56%
See 1 more Smart Citation
“…Activation of Piezo1 exerts an anti-inflammatory effect through inhibition of the NF-κB pathway, but not the extracellular signal-regulated kinase (ERK) and p38 pathways (Malko et al, 2023). Consistent with this, showed that inhibition of Piezo1 promotes LPSmediated secretion of pro-inflammatory cytokines from microglia.…”
Section: Piezo1 Regulates the Inflammatory Phenotype Of Microgliasupporting
confidence: 56%
“…In the brain, in the presence of inflammation-stimulating factors (Aβ or LPS), activation of Piezo1 tends to suppress the pro-inflammatory phenotype of glial cells. Malko et al (2023) showed that 0.3-3 μM Yoda1 inhibited LPS-induced microglial activation and production of the pro-inflammatory factors TNF-α and IL-6, which could be abolished by GsMTx4 or siPiezo1RNA.…”
Section: Piezo1 Regulates the Inflammatory Phenotype Of Microgliamentioning
confidence: 98%
“…Considering our findings, shear stress-potentiated NFAT translocation should be independent of Piezo1 but regulated by CRAC/Orai1 channels. Interestingly, in microglial cells, considered the major immune cell type in the brain, activation of NFAT proteins is also independent of Piezo1 57 . In many other cell types, however, we noticed that Piezo1-mediated mechanosensing is linked to activation of the NFAT family, including macrophages 58 , osteoblasts 59 , erythroblasts 60 , colon cancer stem-like cells 61 , and cardiomyocytes 62 .…”
Section: Discussionmentioning
confidence: 99%
“…As nuclear targets of MAPKs pathways, NF‐κB occupies a key position in the inflammatory response process. When cells are activated by signals, they respond by activating NF‐κB by promoting the phosphorylation and degradation of I‐κB 31 . Then, the activated NF‐κB is translocated into the nucleus, resulting in the transcriptional expression of genes correlated with cellular growth properties 32 .…”
Section: Discussionmentioning
confidence: 99%